ANALYSIS OF THE TAMBAHAN PENGHASILAN PEGAWAI-TPP (ADDITIONAL EMPLOYEE INCOME) ON EMPLOYEE PERFORMANCE IN THE GOVERNMENT OF THE CITY OF BANJARMASIN - Sri Yulia Irvana; Muslih Amberi; Rahma Yuliani (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
One of the government's tasks is to provide fair and decent salaries and ensure the welfare of civil servants. In addition to salaries, civil servants are given allowances and other facilities based on statutory regulations. The provision of additional employee income to employee performance within the Banjarmasin City Government is expected to improve performance and employee productivity, and improve employee welfare. The purpose of this study was to determine the provision of additional employee income to improve employee performance and the factors that support and inhibit this policy. The research approach used in this research is a qualitative approach. The type of research used is descriptive qualitative. To explore information on the provision of additional employee income, the authors determine informants, including the Mayor of Banjarmasin, the Regional Secretary of the City of Banjarmasin, and the Pokja Team for Providing Additional Employee Income at the Banjarmasin City Government and employees within the Banjarmasin city government. The results of this study indicate that the provision of additional employee income within the Banjarmasin City Government has increased employee performance and productivity and obtained the factors that support and hinder this policy based on performance indicators according to Dwiyanto (2006) namely: Productivity, Service Quality, Responsiveness, Responsibility, and Accountability. The five performance indicators have improved and affected employee performance by providing additional income.